Kemandirian Belajar Siswa Melalui Model Pembelajaran Kooperatif Think Pair Square (TPSq) - Gusnita; Melisa; Hafizah Delyana (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2021)
Lack of self-regulated learning is the background of this research. The research objective was to determine how independent student learning was after applying the Think Pair Square type of cooperative learning model. Qualitative descriptive is a type of research using an instrument in the form of an independent learning questionnaire. The subjects in this study were class XI RPL B students of SMK Negeri 1 Bukit Sundi who were registered in the 2019/2020 school year. Based on data analysis with data descriptions, it was found that student learning independence for each indicator was at a percentage of more than 59%. With strong criteria. So, it can be concluded that the students' learning independence is strong after applying the Think Pair Square cooperative learning model.